Small-Scale Food Processing's Role in Farm to Institution: Filling Market Gaps and Moving Toward a Regional Supply Chain - Flagg, Laura. (2018)
Abstract: This thesis explores the challenges and opportunities of small-scale food processing in farm to institution, and analyzes the role that small-scale food processing plays in filling market gaps and moving toward a regional supply chain. This role is examined through a literature review, interviews with farm to institution experts, case studies of three small-scale food processors in the Northeast Region, and an in-depth look at the work CommonWealth Kitchen (CWK), a food business incubator and small-scale food processor in Boston, is doing around institutional contract manufacturing. This thesis finds that there are similar challenges with food processing in farm to institution as there are with procurement of fresh food, but there are also unique challenges such as buyer habits, funding, and scaling up. It also finds that local procurement laws and mandates have good intent, but they are not strong enough to create major change within the farm to institution movement. One of the most significant findings is the need to reframe the conversation around farm to institution to emphasize the positive economic impact that small-scale food processing can have on the regional economy. Recommendations based off of these findings are made for multiple stakeholders in the movement, with the intent of moving small-scale food processing forward.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Jon Witten.; Keywords: Public policy, Social research, and Urban planning.